2012
DOI: 10.1016/j.firesaf.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Flame suppression ability of metallocenes (nickelocene, cobaltcene, ferrocene, manganocene, and chromocene)

Abstract: This article reports experimental investigation of flame suppression ability of metallocenes. In this study, chromocene (CrCp2), manganocene (MnCp2), ferrocene (FeCp2), cobaltcene (CoCp2), and nickelocene (NiCp2) are used. The experiments are conducted by combusting a filter paper on which the metallocene is absorbed, by thermogravimetric measurement for metallocene/cellulose systems, and by burning a solution of the metallocene in n-pentane. Their suppression abilities are characterized with three parameters:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…It should be noted that while higher ferrocene fractions decrease the extinguishing efficiency [18], the experimental results obtained in this study imply that high-performance O/W emulsions containing higher amounts of 500-ppm ferrocene can be produced by increasing the amount of n-octane, as the extinguishing capability of ferrocene exceeds its flammability.…”
Section: Suppression Experimentsmentioning
confidence: 53%
See 1 more Smart Citation
“…It should be noted that while higher ferrocene fractions decrease the extinguishing efficiency [18], the experimental results obtained in this study imply that high-performance O/W emulsions containing higher amounts of 500-ppm ferrocene can be produced by increasing the amount of n-octane, as the extinguishing capability of ferrocene exceeds its flammability.…”
Section: Suppression Experimentsmentioning
confidence: 53%
“…However, it is known that higher ferrocene fractions decrease the suppression efficiency [18]. For instance, Linteris et al numerically and experimentally demonstrated that the extinguishing efficiency dramatically decreases at high iron fractions, which is owing to the agglomeration and condensation of the active iron species [7].…”
Section: Suppression Experimentsmentioning
confidence: 99%
“…The In‐Fe structure is similar to that of ferrocene. Several studies have reported that ferrocene can promote flame extinction and suppress smoke production by accelerating char formation …”
Section: Resultsmentioning
confidence: 99%
“…Due to the outstanding suppression effect, chemical powders have become a new research focus in the field of gas explosion suppression. Among them, SiO 2 , NH 4 H 2 PO 4 , CaCO 3 , NaHCO 3 , KHCO 3 , Al(OH) 3 , Fe(OH) 3 , Mg(OH) 2 , NaCl, CO(NH 2 ) 2 , diatomite and red-mud [7][8][9][10][11][12][13][14][15][16][17] have been widely investigated as gas explosion inhibitors. The results show that these materials have different inhibition performances on gas explosion.…”
Section: Introductionmentioning
confidence: 99%